2006
DOI: 10.1016/j.jcrysgro.2005.12.112
|View full text |Cite
|
Sign up to set email alerts
|

White organic electroluminescent devices

Abstract: This study investigates energy transfer between N,N 0 -bis-(1-naphthyl)-N,N 0 -diphenyl-1,1-biphenyl-4-4 0 -diamine (NPB) host material and 4-dicyanomethylene-2-methyl-6-[2-(2,3,6,7-tetrahydro-1H,5H-benzo[ij]quinolizin-8-yl) vinyl]-4H-pyran (DCM2) fluorescent dye in organic electroluminescent (OEL) devices to produce white-color emission. Bathocuproine (BCP) was applied as a hole-blocking layer (HBL) due to its significantly large HOMO, while tris-(8-hydroxy-quinoline) aluminum (Alq 3 ) was employed in the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…5b). Similar photoluminescence maximum shift was observed for DCM molecules in various dielectrics constant solvents 14,15 (see Fig. 6d).…”
Section: Absorption and Light Emission Propertiessupporting
confidence: 82%
See 1 more Smart Citation
“…5b). Similar photoluminescence maximum shift was observed for DCM molecules in various dielectrics constant solvents 14,15 (see Fig. 6d).…”
Section: Absorption and Light Emission Propertiessupporting
confidence: 82%
“…c) Photoluminescence maximum wavelength of DCM compound in various dielectric constant solvents. 14,15 Lines are guideline for eyes These values are larger compared to experimentally measured optical dielectric constant of 2.22 for PMMA. 18 It means that dielectric constant of the system was increased by increasing the amount of the active molecules.…”
Section: Absorption and Light Emission Propertiesmentioning
confidence: 68%
“…All measurements were carried out at room temperature under ambient conditions. energy transfer can happen from NPB to Alq 3 or from Alq 3 to DCJTB [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Methodsmentioning
confidence: 99%
“…The key advantages of organic light-emitting diodes (OLEDs) for flat panel display applications are their self emitting property, high luminous efficiency, full colour capability, wide viewing angle, high contrast, low power consumption, low weight and potentially large, which are a colour displays and flexibility [1][2][3][4][5][6][7][8][9][10]. In 1987,Tang et al reported a stacked EL cell structure, which has a luminescent efficiency of 1.5 lm/W and a luminance of 1000 cd/m 2 for green light under lower operating voltage than 10V [1].…”
Section: Introductionmentioning
confidence: 99%